THE ESSENCE OF PSYCHOLOGICAL AND PEDAGOGICAL CHARACTERISTICS OF COGNITIVE ACTIVITY IN TEACHING STUDENTS (Conference Zone, 2022)
This article discusses the importance of the psychological and pedagogical features of cognitive activity in the teaching of higher education students.